MGNREGA, paid work and women’s empowerment - Bárcia de Mattos, Fernanda; Dasgupta, Sukti (Geneva, 2017)
"Southern Asia is one of the regions where gender gaps are most stark. Indeed in India, as in other parts of the region, few women are able to access paid employment. This paper explores the impacts of the legislated right to work in rural India on women’s employment. It reviews trends in women’s engagement in the public works programme as well as whether this work contributes to their empowerment and bargaining power in the household. It also examines the extent to which these impacts are transformational by assessing whether girls in the household are affected by women’s employment outside of the home."